Cu and Pb Co-Contamination Accelerates the Decomposition Rate of Litter from Invasive Aquatic Plant Eichhornia crassipes (Mart.) Solms and the Effect Increases with Its Invasion Degree - Yizhuo Du; Yingsheng Liu; Xiaoxuan Geng; Yue Li; Chuang Li; Yulong Zhang; Congyan Wang; Daolin Du (Horticulturae)
Invasive and native plants can coexist in the same ecosystem. Thus, the fallen leaves of invasive and native plants can be mixed, which can lead to co-decomposition. Invasive plants can create microenvironmental conditions conducive to their invasion process by influencing soil physicochemical properties, soil nutrient contents, and soil enzymatic activities through litter decomposition by released metabolites. Heavy metal contamination may affect the litter decomposition of invasive plants. This study was designed to elucidate the effects of the mono- and co-decomposition of the leaves of the invasive aquatic plant Eichhornia crassipes (Mart.) Solms (Common Water Hyacinth) and the native aquatic plant Nymphaea tetragona Georgi (Pygmy Water-Lily) on soil physicochemical properties, soil nutrient contents, and soil enzymatic activities under the mono- and co-contamination of Cu and Pb. This study was conducted over a six-month period using a polyethylene litter bag experiment. The type of heavy metals may be the most significant factor influencing the differences in the decomposition rate between E. crassipes and N. tetragona. The co-contamination of Cu and Pb increased the decomposition rate of the leaves of E. crassipes and the decomposition rate also increased as the invasion degree of E. crassipes increased relative to N. tetragona. The co-decomposition of the leaves of the two aquatic plants showed an antagonistic response under the mono-contamination of Pb and the control, but presented a synergistic response under the mono-contamination of Cu and the co-contamination of Cu and Pb, regardless of the invasion degree of E. crassipes. Soil enzymatic activities, especially the activities of polyphenol oxidase and cellulase, may be a significant factor influencing the litter decomposition of the two aquatic plants. Consequently, heavy metal contamination may affect the invasion process of E. crassipes with regard to the regulation of the released metabolites during the decomposition process, and this is specifically modulated by the type of heavy metals.